Media Internet, Koran, dan Majalah Berbahasa Arab dalam Pembelajaran Tarjamah di Kelas Prodi PBA Jurusan Tarbiyah STAIN Purwokerto - Ali Muhdi (IAIN Purwokerto, 2014)
Abstract: In learning translation, themes or texts selection from internet media,newspapers, and magazines are more attractive over from the classics or bookspurely religious texts. The Internet, newspapers, and magazines represents thefaster change and development of language that actual in communities, as well asover-accommodative adaptive to new vocabularies of contemporary and popular.Similarly, the responses of the students feel more comfortable to use materials fromthe Internet, newspapers, and magazines in Arabic Translations in the learningprocess. They are more interested because the texts are more able to absorb theactuality of discourse or emerging opinion. As well as the variations of the themethat made the students do not get bored with the learning process that takes place.Keywords: Media, Internet, newspapers, magazines, translation. Abstrak: Proses pembelajaran tarjamah bahasa Arab dimulai dengandiberikannya pengantar tentang teori atau beberapa konsep dasar penerjemahanbahasa Arab yang baik berikut langkah yang mudah dan praktis. Respon paramahasiswa terhadap media internet, Koran, dan majalah berbahasa Arab dalamproses pembelajaran Tarjamah adalah merasa senang dan lebih tertarik jika materiteks tarjamah berasal dari media internet/koran/majalah berbahasa Arab. Alasanmereka jika dibandingkan teks yang berasal dari kitab-kitab klasik, teks darimedia internet, koran, majalah, atau media modern lainnya lebih bisa menyerapaktualitas wacana atau opini yang sedang berkembang. selain itu, ada variasitema yang menjadikan para mahasiswa tidak merasa bosan karena selalu adahal baru dan menarik yang diperbincangkan atau didiskusikan di dalam kelas.Kata Kunci: Media, Internet, koran, majalah, penerjemahan.